1984
DOI: 10.1136/gut.25.8.863
|View full text |Cite
|
Sign up to set email alerts
|

Adenomas of the large intestine after cholecystectomy.

Abstract: SUMMARY The frequency of adenomas of the large intestine in 331 cholecystectomised patients who underwent total colonoscopy was compared with that of a control group of patients with asymptomatic cholelithiasis who were matched for age and sex. Whereas no significant difference in the frequency of adenomas was found between these two groups, a subgroup of patients aged 60-80 years with a postcholecystectomy interval of 10 years or greater exhibited a significantly (p<0-05) greater frequency of adenomas (38.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In addition, age might play a role. This is suggested by the results of a study [28] including more than 4,000 patients who underwent colonoscopy; the incidence of cancers and adenomatous polyps of the colon was significantly in creased if the patient's age was 60-80 years and if the post-CE interval was longer than 10 years. However, our study could not dem onstrate a higher frequency of large bowel cancer in cholecystectomized cases at a higher age.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, age might play a role. This is suggested by the results of a study [28] including more than 4,000 patients who underwent colonoscopy; the incidence of cancers and adenomatous polyps of the colon was significantly in creased if the patient's age was 60-80 years and if the post-CE interval was longer than 10 years. However, our study could not dem onstrate a higher frequency of large bowel cancer in cholecystectomized cases at a higher age.…”
Section: Discussionmentioning
confidence: 87%
“…Concern, however, has risen about the hypothesis, that cholecystectomy might in-crease formation and pool size of secondary bile acids, mainly DCA (3)(4)(5). Several studies have reported an increased incidence of colonic neoplasia 6-15 yr after cholecystectomy (6)(7)(8). Even though not confirmed by others (9,10), this observation has been linked to the cocarcinogenic role of excess DCA observed in animal experiments (1 1,12).…”
Section: Introductionmentioning
confidence: 86%
“…Some studies have found an increased risk in proximal colon cancer associated with cholecystectomy [4,12,45,68,72,79,80,82], and in many cases where the risk of right sided colonic cancer has been looked at the association is strongest in women [15,22,51,58,59,62,65,73,75]. Other studies have found an overall increased susceptibility to colorectal carcinoma at any site in both men and women [5,43,44,52,55], or mainly in the rectum [13]. Most of the studies in women have been in young women [47,48], but the risk has also been found to be high in older women [68].…”
Section: Discussionmentioning
confidence: 96%